Workshop on Capacity Strengthening of Innovative and Dedicated School Principals at The Work Deliberation Forum for High School/Vocational Schools in West Manggarai with Problem-Solving Simulation Model (PSSM) - Regus, Maksimus; Sawan, Fransiskus; Tapung, Marianus (CV. Green Publisher Indonesia, 2025)
This research describes the implementation of the Workshop on Strengthening the Capacity of Innovative and Dedicative Principals in the Forum of Senior High School/Vocational High School Principals in West Manggarai using the Problem-Solving Simulation Model (PSSM). This activity was designed to address the gap in education quality in West Manggarai. The objectives of the workshop were to improve principals' leadership skills, develop contextual solutions to educational problems and build collaborative networks among principals. The workshop was conducted through four systematic stages: Problem Identification, Reflection, Evaluation, and Follow-up. Through the PSSM approach, the principals analyzed problems, developed contextual solutions, and simulated their implementation. The workshop successfully increased the capacity of 42 principals with a 68% increase in understanding of transformational leadership. Participants produced 10 innovative action plans based on the local context and formed five peer mentoring groups for program sustainability. The level of participant satisfaction reached 87% based on the end-of-program evaluation. The collaboration with Universitas Katolik Indonesia Santu Paulus Ruteng plays a strategic role in providing academic assistance and creating a sustainable learning ecosystem to improve the quality of education in West Manggarai.